2015
DOI: 10.1039/c5tb00713e
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of the fast setting and suitable degrading Ca–Si–Mg cement on both cementogenesis and angiogenesis differentiation of human periodontal ligament cells

Abstract: The purpose of this study is to develop a fast setting and suitable degrading Mg-calcium silicate cement (Mg-CS) and a mechanism using Mg ions to stimulate human periodontal ligament cells (hPDLCs).Mechanical strength and stability have been determined by testing the diametral tensile strength; the degradation of cements has been measured by ascertaining the number of ions released in simulated body fluid. Other cell characteristics such as proliferation, differentiation and mineralization, and hPDLCs when cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Although the mechanism of the composite scaffolds‐induced differentiation and mineralization of hDPCs is not clear yet, it seems reasonable to postulate that the release of ionic products from Biodentine, together with the apatite‐forming ability, might play vital roles in manipulating the differentiation and mineralization of hDPCs (Chen et al . , ). Considering the excellent bioactivity and biological performance of the composite, the bioactive scaffold fabricated with 3D printing techniques could be a suitable scaffold for guiding dental and bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of the composite scaffolds‐induced differentiation and mineralization of hDPCs is not clear yet, it seems reasonable to postulate that the release of ionic products from Biodentine, together with the apatite‐forming ability, might play vital roles in manipulating the differentiation and mineralization of hDPCs (Chen et al . , ). Considering the excellent bioactivity and biological performance of the composite, the bioactive scaffold fabricated with 3D printing techniques could be a suitable scaffold for guiding dental and bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous types of available biomaterials, ceramics are among the more prominent candidates for bone substitutes. Of which, calcium silicate (CS) is one of the more popular bioceramics due to its excellent biodegradation and osteoconduction ability as compared to the rest of the ceramics [8][9][10]. Recently, bone cements made up of calcium silicate received great attention from researchers as reports indicated that CS had the capability to release therapeutic ions such as Si and Ca ions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The improvements of apatite formation were attributed to more n-MS exposing on the surfaces of both PCP and PCPS, which induced more apatite formation. The mechanism of apatite formation on these samples was similar to that of the n-MS based composites in SBF, 28 which was shown as following: After immersed into SBF, the Ca ions released from the samples due to the slight dissolution of n-MS, which exchanged with H 3 O + in solution, and then Si-OH formed. After that, the Ca 2+ was attracted onto the sample surface by electrostatic action, and then PO 4…”
Section: Discussionmentioning
confidence: 73%